Overview of Factors Affecting the Implementation of Integrated Healthcare Center (Posyandu) - Mahreza, Desviana Putri Eka; Lahdji, Aisyah; Anggraini, Merry Tiyas (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: One of the health facilities provided by the government is integrated health center in the village or Pos Pelayanan Terpadu or Posyandu. The impact of  posyandu that does not run smoothly will result in a decline in the quality of public health. The purpose of this study is to provide an overview of the factors that influence the implementation of posyandu in Kaliboto Lor Village, Jatiroto District, in 2020.Method: The research was carried out with descriptive observation and also qualitative design. The sampling technique used is snowball sampling with a total sample of 6 people. The research was conducted from October to November 2021.Result: The research found that the implementation of posyandu in Kaliboto Lor Village, Jatiroto District could not be carried out every month due to restrictions on activities and the application of health protocols. There are supporting factors, including parties’ participation, infrastructure facilities, good coordination, the existence of coaching, and evaluation of activities. Inhibiting factors include non-optimal use of the forum, limited posyandu targets, lack of commitment from parties, and an unsupportive environment. The efforts made are counseling, home visits, appointments, and monitoring of periodic evaluations. There is no significant difference between the implementation of posyandu with the previous year.Conclusion: In general, the implementation of posyandu is still not optimal due to the constrained method and the need for a follow-up plan from the puskesmas. The research results obtained can be used as a reference in improving the performance of posyandu.